The first record of Egglestonichthys bombylios (Gobiiformes: Gobiidae) from China with its first fresh colouration information - Ni, Yong; Wu, Hanlin; Chen, Yuange; Chen, Jiajie; Tian, Wei; Chen, Weifeng; Xu, Zhaoli; Zhong, Junsheng (Zootaxa, 2024)
During bottom trawl surveys carried out between 2013–2021, 52 specimens (33.8–54.0 mm SL) of Egglestone’s bumblebee goby Egglestonichthys bombylios were collected at a depth of 1.5–15 m from Dongshan Bay, Sanmen Bay, and Niushan Island, China. They represent the first records of this species from China. A full description, including fresh colouration of the species is provided as it is poorly known. The individuals collected in China agree with most morphological features of the holotype, except for the pelvic fin fraenum that was not observed or appears to be absent in most specimens. A strong relationship between E. bombylios, Larsonella pumilus, and the genus Priolepis is herein demonstrated by the mitochondrial genome sequences of E. bombylios and twenty closely related species. This study enriches the existing genetic data of the so-called Priolepis lineage and provides useful insights into the phylogenetic relationships across species of the genera Egglestonichthys, Priolepis, and Larsonella.